Training and Simulation of German Oral Examination A2 Level with the Moodle-based Mix Method for High School Students in Bogor Region - Oktapiani, Widia; Hendra, Dani; Amir, Amir; Nurhani, Nuki; Hafdarani, Hafdarani (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2025)
This community service activity aims to improve the understanding and ability of SMA/SMK students in Bogor and surrounding areas in facing the oral exam German language level A2 (Goethe-Zertifikat A2: Fit in Deutsch), in preparation for the National German Olympiad. National German Olympiad. Through a blended learning approach, the training training was conducted online using the LMS platform Moodle LMS platform and offline through live simulations. The training includes an introduction to the exam format, practice questions, and oral exam simulation. The results of the activity showed a significant increase in in student comprehension, with the average score of the of the oral exam increased from 16% to 72%. Implementation of Moodle in this activity was effective in preparing students for the online oral exam and supports improving the quality of German language learning. The results of this activity is expected to be an inspiration for the implementation of similar programs in the future.